A Study of Small Shareholders' Attitude towards Small-shareholder Activism. Issue 1 (June 2016) - Sharma, Sunita Upendra
Abstract: Rights, duties and liabilities of all stakeholders are explicitly enshrined in the new companies' legislation, but the real issue is whether such rights are asserted by various stakeholders, especially the small shareholders, effectively in their own interest. The foundation of shareholder activism lies on the premise of uncompromising attitudes of investors to protect their hard-earned money. This empirical article, therefore, explores the attitude of small shareholders about small-shareholder activism. This article further seeks to analyse and develop a model establishing relationships, if any, between various concepts related with small-shareholder activism. Descriptive and non-parametric analysis of data shows that though legal environment for small-shareholder activism is quite favourable in India, the small shareholders' reliance on regulatory bodies, major competitive shareholders and financial institution for their protection makes them docile investors and they would prefer to exit or remain loyal than resorting to shareholder activism.